Aging in Brazil. (21st March 2018) - Tramujas Vasconcellos Neumann, Lycia; Albert, Steven M
Abstract: The population in Brazil is aging at a fast pace and in a context of historical socioeconomic and regional disparities. In the last decades, the country has developed important policies and legal mechanisms to guarantee older adults' right to age well and with dignity. The implementation of these policies and laws, however, has been slow and hampered by lack of coordination and resources. With an estimate of 64 million seniors living in the country by 2050, Brazil has important public policy issues to address, such as the poor implementation of the National Policy of the Elderly, the urgency of Social Security Reform, and the need for a comprehensive long-term care policy for older adults.